Sodium-glucose cotransporter 2 inhibition: which patient with chronic kidney disease should be treated in the future? - Neuen, Brendon L (Nephrol Dial Transplant, 2020)
The advent of sodium-glucose cotransporter 2 (SGLT2) inhibitors represents a major advance for people with type 2 diabetes (T2DM) and chronic kidney disease (CKD). The results of the Canagliflozin and Renal Events in Diabetes with Established Nephropathy Clinical Evaluation (CREDENCE) trial have clearly demonstrated that canagliflozin prevents kidney failure and cardiovascular events. The results from three other large-scale randomized trials, collectively enrolling >30 000 participants, have provided further evidence that the effects of SGLT2 inhibition on major kidney outcomes in people with T2DM may be present across the class, although this will only be known for certain when Dapagliflozin and Renal Outcomes and Cardiovascular Mortality in Patients with CKD (DAPA-CKD) (NCT03036150) and The Study of Heart and Kidney Protection with Empagliflozin (EMPA-KIDNEY) (NCT03594110) are reported over coming years. Importantly, the benefits of SGLT2 inhibition have been achieved in addition to the current standard of care. This review summarizes evidence for SGLT2 inhibition in people with T2DM and CKD, evaluates key patient characteristics and concomitant drug use that may influence the use of these drugs in people with CKD, discusses current guideline recommendations and explores how these drugs may be used in people with CKD in the future, including in combination with other treatments.